See it again, say it again: The artist as researcher - Wesseling, Janneke (Amsterdam Valiz Antennae Series, 2011)
More often than not, a work of art is produced through a dialectic of action and reflection--a zooming into and out of the material at hand (be it physical or conceptual) that eventually arrives at a synthesis of the two drives. See It Again, Say It Again explores this process of reflection and research within the making of an art work. Does it lead to better art? What do artists actually do when they engage in research? The book includes essays by artists and theorists Janneke Wesseling, Jeroen Boomgaard, Jeremiah Day, Stephan Dillemuth, Irene Fortuyn, Gijs Frieling, Henri Jacobs, W.J.M. Kok, Aglaia Konrad, Frank Mandersloot, Aernout Mik, Ruchama Noorda, Vanessa Ohlraun, Graeme Sullivan, Moniek Toebosch, Lonnie van Brummelen & Siebren de Haan, Hilde Van Gelder, Philippe Van Snick, Barbara Visser, Kitty Zijlmans and Italo Zuffi.